2017
DOI: 10.1111/brv.12342
|View full text |Cite
|
Sign up to set email alerts
|

The comparative study of empathy: sympathetic concern and empathic perspective‐taking in non‐human animals

Abstract: While empathy is a century-old psychological concept, its study in non-human animals has become the focus of much recent scientific interest, as it promises to provide the clues to understand the evolutionary origins of our social and moral nature. A review of the comparative study of empathy is thus timely to complement and constrain anthropocentric views, and to integrate current findings. However, this is not an easy task. The study of animal empathy has developed using different paradigms, different concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 162 publications
(322 reference statements)
1
56
0
1
Order By: Relevance
“…Occasionally among baboons, close relatives/male friends have been observed to guard an infant's body while the mother forages, and individuals will band together to defend the corpse (Cheney & Seyfarth, ). Guarding responses share behavioural traits with sympathetic concern and empathetic targeted helping (Pérez‐Manrique & Gomila, ), and appear to be part of an evolved set of compassionate responses derived from neurophysiological mechanisms dedicated towards mother–infant bonding and cognitive mechanisms involved with kin‐based and alliance‐based based associations (reviewed in Gilbert, ).…”
Section: Primate Thanatology: Contemporary Reportsmentioning
confidence: 99%
“…Occasionally among baboons, close relatives/male friends have been observed to guard an infant's body while the mother forages, and individuals will band together to defend the corpse (Cheney & Seyfarth, ). Guarding responses share behavioural traits with sympathetic concern and empathetic targeted helping (Pérez‐Manrique & Gomila, ), and appear to be part of an evolved set of compassionate responses derived from neurophysiological mechanisms dedicated towards mother–infant bonding and cognitive mechanisms involved with kin‐based and alliance‐based based associations (reviewed in Gilbert, ).…”
Section: Primate Thanatology: Contemporary Reportsmentioning
confidence: 99%
“…However, many non-human animals use their brains to make complex decisions, plan for the future, have concepts of objects that are not present, use tools, communicate, deceive, and show empathy [4]. Examples of empathy include a chimpanzee responding to another during childbirth, a dolphin lifting a human swimmer in difficulty or a sick dolphin, and a pet dog responding to another individual that is in pain; some of these are shown in [7][8][9]. The basic concepts of biology are the same for humans and other species and almost all biological systems occur in all vertebrates, including humans, so if each human is considered important, each other vertebrate individual could reasonably be considered to be important [10].…”
Section: Who Are We?mentioning
confidence: 99%
“…Death-related behaviour is described as a subcategory of epimeletic or nurturant behaviours (i.e. a healthy individual gives attention to an injured or dead one, as summarized in [4]) and is usually seen as a consequence of the cooperative, succouring and protective nature of social mammals [4][5][6][7][8]. Considering that the individual receiving this attention is often an offspring, some authors suggested that this behaviour could be a consequence of the strong mother-offspring bond [9][10][11][12], or a revival attempt through violent manipulation of the bodies [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In cases where individuals were unable to carry the dead (e.g. lemurs, giraffes and elephants), these species are known to stay near a dead conspecific for extended periods and move back and forth between their groups and their distressed or dead offsprings [6][7][8]. Many aquatic mammal species react to the death of a conspecific, most often a calf, and adults can be observed staying close to, maintaining physical contact with, lifting, keeping at the surface or carrying the dead one, even in an advanced state of decomposition.…”
Section: Introductionmentioning
confidence: 99%